2020
DOI: 10.1002/anie.202001531
|View full text |Cite
|
Sign up to set email alerts
|

Nanocatalosomes as Plasmonic Bilayer Shells with Interlayer Catalytic Nanospaces for Solar‐Light‐Induced Reactions

Abstract: Interest and challenges remain in designing and synthesizing catalysts with nature-like complexity at few-nm scale to harness unprecedented functionalities by using sustainable solar light. We introduce "nanocatalosomes"-a bioinspired bilayer-vesicular design of nanoreactor with metallic bilayer shell-in-shell structure,h aving numerous controllable confined cavities within few-nm interlayer space,customizable with different noble metals.T he intershell-confined plasmonically coupled hot-nanospaces within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 54 publications
0
19
0
Order By: Relevance
“…[ 78 ] Besides, polymer‐assisted and template‐supported synthetic methods were also employed to prepare coupled nanostructures, such as Au@SiO 2 dual shell NPs, [ 76 ] Au core–Ag satellite nanostructures, [ 107 ] Au core–satellite nanostructures, [ 108 ] Au‐nanobridged NPs, [ 109 ] porous triple‐shell Au nanostructures, [ 110 ] and hollow bilayer shell Au‐Au/Pd/Pt nanocatalosomes (Figure 8b,c). [ 102 ] Novel plasmonic coupling properties and excellent catalytic activities were obtained by using these unique coupled nanostructures.…”
Section: Design and Manipulation Of Structures For Plasmonic Couplingmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 78 ] Besides, polymer‐assisted and template‐supported synthetic methods were also employed to prepare coupled nanostructures, such as Au@SiO 2 dual shell NPs, [ 76 ] Au core–Ag satellite nanostructures, [ 107 ] Au core–satellite nanostructures, [ 108 ] Au‐nanobridged NPs, [ 109 ] porous triple‐shell Au nanostructures, [ 110 ] and hollow bilayer shell Au‐Au/Pd/Pt nanocatalosomes (Figure 8b,c). [ 102 ] Novel plasmonic coupling properties and excellent catalytic activities were obtained by using these unique coupled nanostructures.…”
Section: Design and Manipulation Of Structures For Plasmonic Couplingmentioning
confidence: 99%
“…[ 53 ] As such, these hot spots allow for higher exciton generation rates at the interfaces between the coupled metal nanostructures and the semiconductor photocatalysts, which are beneficial to plasmonic photocatalytic reactions. [ 102 ] In addition, a larger amount of hot electrons may exist at the hot spots, and could be injected into the molecular orbital of the adsorbed reactants to activate surface redox reactions. [ 62 ] There might be also strong interactions between the dipole moments of the adsorbed reactants and the confined EM field in the hot spots region, that can modify the chemical reaction pathways.…”
Section: Plasmonic Coupling In Solar‐driven Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al have recently reported plasmonic-catalytic nanoreactors named "nanocatalosomes (NCat)", characterized by a metal-bilayer hollow shell-in-shell structure composed of arrays of closely spaced NPs (Figure 9). 98 The interlayer space of NCat presents a large number of plasmonic nanocavities intimately interfaced with the chosen catalytic metal (Au/Pt/Pd). NCat were obtained starting from hollow porous silica nanoshells modified with Au seeds and coated with a 3 nm film of tannic (TA) and iron coordination polymer (TA-Fe).…”
Section: Chemical Science Accepted Manuscriptmentioning
confidence: 99%
“…9 ). 98 The interlayer space of NCat presents a large number of plasmonic nanocavities intimately interfaced with the chosen catalytic metal (Au/Pt/Pd). NCat were obtained starting from hollow porous silica nanoshells modified with Au seeds and coated with a 3 nm film of tannic (TA) and iron coordination polymer (TA–Fe).…”
Section: Catalytic Systemsmentioning
confidence: 99%